The political economy of geographical indications - Koen Deconinck; Johan Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2014)
Despite the growing importance of geographical indications (GI), relatively little attention has been devoted to studying the optimal size of a GI region, as well as how lobbying by interest groups may affect the actual size. We develop a political economy model of the size of geographical indications, taking into account possible effects on perceived quality as well as on cost sharing among producers. We show that the political process may result in a GI area that is smaller or larger than the social optimum, not just depending on the relative political influence of existing and potential producers, but also on how changes in quality affect consumer welfare.
Keywords: 330